PENGALAMAN PASIEN HIPERTENSI PRIMER SUKU MINANG YANG MENJALANI PERAWATAN DI RUMAH - Rina -; Setiawan -; Cholina Trisna Siregar (Fakultas Keperawatan Universitas Andalas, 2016)
Abstract Primary hypertension if not controlled properly at home will develop into secondary hypertension which may cause damage to the target organ. Primary hypertension is often called the